2018
DOI: 10.1002/jsfa.8847
|View full text |Cite
|
Sign up to set email alerts
|

Impact of food processing and simulated gastrointestinal digestion on gliadin immunoreactivity in rolls

Abstract: Enzymatic pre-modification of proteins during the process of dough fermentation decreases their immunoreactive potential, such that fewer peptides recognised by R5 antibodies are released during the digestion process from the bread matrix. Immunoreactive peptides are degraded more effectively when digestive enzymes are supported by the addition of PEP. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Experiments reveal that, after baking, the gliadin quantity is lower whether the bread is obtained from unfermented or fermented dough. However, this effect has not been explicitly reported before, although Brzozowski´s works seem to infer some contribution from the baking process to proteolysis in the bread samples [ 55 ]. Also, Vaquero et al (2018) [ 16 ] found a marked decrease in gliadins in wheat and tritordeum bread after baking, although they did not analyze gliadin content before.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments reveal that, after baking, the gliadin quantity is lower whether the bread is obtained from unfermented or fermented dough. However, this effect has not been explicitly reported before, although Brzozowski´s works seem to infer some contribution from the baking process to proteolysis in the bread samples [ 55 ]. Also, Vaquero et al (2018) [ 16 ] found a marked decrease in gliadins in wheat and tritordeum bread after baking, although they did not analyze gliadin content before.…”
Section: Discussionmentioning
confidence: 99%
“…Since the effects of some other treatments on the secondary and tertiary structure of the gluten were not significant, we only analyzed the structure, digestive properties, and potential allergenicity of phosphorylated and alcalase and papain hydrolyzed gliadins. It had been reported that processing methods could change the allergenicity of allergenic foods, 10,32 and different treatments induced varying degrees of gliadin structural changes, thereby reducing or increasing allergenicity. 16 In our study, the changes in secondary and tertiary structures of raw and treated gluten were determined through FTIR and fluorescence spectra.…”
Section: ■ Discussionmentioning
confidence: 99%
“…α-Gliadin accounts for 15−30% of wheat proteins and is the most abundant of the gliadins. 10 There are many allergens that have been found in wheat flour. Different types of wheat proteins cause different allergy symptoms, such as asthma and rhinitis, known as immunoglobulin E mediated inhalation of flour allergy.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other prolyl endopeptidases (PEPs) isolated from Myxococcus xanthus and Flavobacterium meningosepticum showed the ability to hydrolyze toxic gliadin peptides significantly. However, the presence of immunopeptides has not been determined [ 72 , 73 , 74 , 75 ]. PEPs from Sphingomonas capsulate, showed complete hydrolysis of immunogenic gluten peptides after mixing with barley cysteine endoproteases [ 17 , 76 ].…”
Section: Dietary Interventions For Complementing the Gfd And Beyondmentioning
confidence: 99%